1987
DOI: 10.1038/325445a0
|View full text |Cite
|
Sign up to set email alerts
|

The GTP-binding protein, Go9 regulates neuronal calcium channels

Abstract: In neuronal cells, opioid peptides and opiates inhibit neurotransmitter release, which is a calcium-dependent process. They also inhibit adenylyl cyclase, presumably via the membrane signal-transducing component, Gi, a guanine nucleotide-binding protein (G-protein). No causal relationship between these two events has yet been demonstrated. Besides Gi, membranes of neuronal tissues contain large amounts of Go, a G-protein with unknown function. Both G-proteins are heterotrimers consisting of alpha-, beta- and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
337
1
2

Year Published

1987
1987
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 890 publications
(354 citation statements)
references
References 31 publications
14
337
1
2
Order By: Relevance
“…Pertussis toxin (PTX, a bacterial exotoxin that blocks the receptor-mediated activation of certain G proteins, notably G i and G o , through the ADP ribosylation of the α-subunit) interferes with the norepinephrine (NE) and GABA receptormediated inhibition of Ca 2+ currents recorded from dorsal root ganglion (DRG) neurons 16 . Similarly, PTX also blocks the inhibitory actions of the enkephalin analog D-Ala-D-Leuenkephalin (DADLE) and somatostatin on Ca 2+ currents recorded from the neuroblastomaglioma cell line NG108-15, and the pituitary cell line AtT20, respectively 13,17 . As mentioned above, activation of G proteins is terminated by hydrolysis of the bound GTP.…”
Section: G Proteins As Regulators Of Ca 2+ Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pertussis toxin (PTX, a bacterial exotoxin that blocks the receptor-mediated activation of certain G proteins, notably G i and G o , through the ADP ribosylation of the α-subunit) interferes with the norepinephrine (NE) and GABA receptormediated inhibition of Ca 2+ currents recorded from dorsal root ganglion (DRG) neurons 16 . Similarly, PTX also blocks the inhibitory actions of the enkephalin analog D-Ala-D-Leuenkephalin (DADLE) and somatostatin on Ca 2+ currents recorded from the neuroblastomaglioma cell line NG108-15, and the pituitary cell line AtT20, respectively 13,17 . As mentioned above, activation of G proteins is terminated by hydrolysis of the bound GTP.…”
Section: G Proteins As Regulators Of Ca 2+ Channelsmentioning
confidence: 99%
“…As mentioned above, activation of G proteins is terminated by hydrolysis of the bound GTP. Intracellular application of the non-hydrolysable GTP analog, GTP-γ-S, converts the normally reversible responses to agonist in these cells into irreversible responses 13,17,18 . In contrast, intracellular application of the GDP analog GDP-β-S (which competes with GTP for the nucleotide binding site) blocks the inhibitory actions of NE and DADLE on Ca 2+ currents recorded from DRG and NG108-15 cells, respectively 13,16 .…”
Section: G Proteins As Regulators Of Ca 2+ Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect can be demonstrated with opioid peptides in neuroblastoma cells where it has been specifically shown that the pertussis toxin block can be prevented by intracellular application of Gi and G,, the latter effect of G, being 10 times more potent than Gi [17]. This is further supported from the evidence that rat brain G, is a substrate of pertussis toxin ADPribosylation [ 181.…”
Section: Discussionmentioning
confidence: 61%
“…For other effectors the situation is even less clear: ac with GTPyS bound activates Ca2+ channels (Yatani et al, 1987b), but other ac subunits are also effective (Hescheler et al, 1987). The G proteins that regulate polyphosphoinositide-specific phospholipase C are particularly elusive, with evidence for regulation by both pertussis toxin-sensitive and -insensitive G proteins (Taylor & Merritt, 1986;Harden, 1989).…”
Section: G Proteins and Effector Systemsmentioning
confidence: 99%